Assessment of HPV 16, HPV 18, p16 expression in advanced stage laryngeal cancer patients and prognostic significance, - Dogantemur,Selman (2020)
Abstract Introduction: Human papilloma virus is an etiological risk factor for a subset of head and neck squamous cell carcinomas. HPV has been proven to be a powerful prognostic biomarker for oropharyngeal cancer, but its role in the larynx has not been explored in depth. The developmental mechanisms of laryngeal carcinomas are quite complex and controlled by various factors. Smoking and alcohol are most important risk factors. Recent studies indicate that HPV infection also plays an important role in larynx carcinomas. HPV related laryngeal carcinomas especially occur at the supraglottic region of larynx. Objective: We aimed to determine the frequency of HPV/protein16 positivity in patients with laryngeal carcinoma and association of HPV and/or p16 positivity with variables such as age, sex, smoking habits, tumor localization, lymph node metastasis, recurrence and survival in advanced stage laryngeal carcinoma in our study. Methods: This retrospective study included 90 patients with advanced laryngeal carcinoma. The Control group was 10 normal larynx mucosa specimens. The presence of HPV was investigated polyclonally by polymerase chain reaction, and protein16 with immunohistochemical method. In HPV positive cases, the presence of HPV types 16, 18 were evaluated by polymerase chain reaction. Demographic features of patients were noted. Patient survival and association with HPV/protein16 was determined. Results: Polyclonal HPV positivity was detected in 11 (12.2%) of 90 cases. Out of these 11 cases, HPV 16 was positive in 6, HPV 18 in 4, and both HPV 16 and 18 were positive in 1. In 18 (20%) of the cases, p16 was positive. Six of the cases (6.6%) had both HPV and protein16 positivity. In cases where protein16 alone or HPV and protein16 were co-positive, alcohol use was less and the tumor was found more likely to be localized in the supraglottic area. These ratios were statistically significant. Supraglottic localization of tumor was determined to be increased in protein16 positive cases. The correlation between protein16 positivity and supraglottic area location was determined to be statistically significant (p= 0.011). 55.6% of protein16 positive cases was located in the supraglottic region, 33.3% was glottic and 11.1% was transglottic. Although life expectancy over 5 years were numerically higher in HPV and protein16 positive cases, this was not found to be statistically significant. There was no statistically significant relationship between HPV positivity and mean age, differentiation, smoking and alcohol use, tumor progression, lymph node metastasis, localization, recurrence, cause of mortality and treatment methods in our study. The mean follow-up period of our patients was 6.7 years. Conclusion: The close relationship between HPV and oropharyngeal squamous cell carcinoma could not be shown in larynx malignancy in many studies, including our study. Our findings support a limited role of HPV in laryngeal carcinogenesis. Protein16 is not a reliable surrogate for HPV status in laryngeal cancers and is not a predictor of laryngeal cancer survival. Supraglottic localization of tumor was determined to be increased in protein16 positive cases. The correlation between protein16 positivity and supraglottic area location was determined to be statistically significant. There is a need for more populated clinical trials, where neoplastic proliferation is better demonstrated and the accuracy of the results obtained is supported by different techniques.